Determinación de Escherichia Coli en el agua del Río Jubones Parroquia La Iberia sector Barrio 10 de Agosto - Loja Retete, Marcela L. (2007)
The present thesis this framed in determine the presence of the bacteria Escherichia Coli in the waters of the River Jerkins, in the sector of the Neighborhood august of the Parish 10 the Iberia. The analyses that were made valued the quality microbiology of the river water that the population of this sector uses.